Lactobacillus casei administration reduces lung injuries in a Streptococcus pneumoniae infection in mice - Racedo, Silvia María (2006)
The effect of the oral administration of Lactobacillus casei on the prevention of a Streptococcus pneumoniae lung infection in a mouse experimental model was studied, analyzing the innate and specific immune response. Adult Swiss albino mice were treated with L. casei (109 CFU/day) for 2, 5 and 7 d. Mice were infected intranasally with S. pneumoniae (106 CFU/mouse) after each treatment and the microbiological, histopathological and host responses were determined for 15 d after infection. Feeding L. casei for 2 d induced a faster clearance of S. pneumoniae, with a lower number of pneumococci in lung and a shorter period of septicemia than in the control group. L. casei administration induced activation of phagocytes as evidenced by the strong myeloperoxidase activity and the nitro blue tetrazolium assay in lung. Mice given L. casei for 2 d showed higher levels of anti-pneumococcal serum IgG and bronchoalveolar lavage IgA than the control mice. The group fed L. casei for 2 d could beneficially regulate the balance between tumor necrosis factor alpha and interleukin 10, allowing a more effective immune response against infection and modulating the inflammatory response, with less damage to the lung. © 2006 Elsevier SAS. All rights reserved.